"Rethink and reset" tourism in the Galapagos Islands: Stakeholders' views on the sustainability of tourism development - Diana V. Burbano; Juan Carlos Valdivieso; Juan Carlos Izurieta; Thomas C. Meredith; Diego Quiroga Ferri (Annals of Tourism Research Empirical Insights, 2022)
Tourism growth in biodiversity conservation areas presents both challenges and opportunities for sustainability. The COVID-19 pandemic brought both into focus in the Galapagos. This study engages with tourism service providers and regulators in Puerto Ayora, Santa Cruz Island, to explore how 'sustainability' has been integrated into evolving links between tourism and conservation since the implementation of the Ecotourism Model a decade ago. Findings suggest that to achieve sustainability, priorities include 1) engaging local stakeholders in a shared vision for tourism development; 2) addressing community concerns, especially regarding basic services, health and education; 3) assessing and managing the balance between "high-end" regulated tourism and low-cost informal tourism. These illustrate challenges and opportunities for sustainable tourism in the Galapagos and elsewhere.
Keywords: 330; Overtourism; Sustainability; Sustainable tourism; Stakeholder perceptions; COVID-19 pandemic; The Galapagos Islands